Shear strengthening of concrete beams: Feasibility of using steel fiber reinforced concrete (SFRC) jacketing (LACCEI, 2024)
A large part of civil works that are carried out involves the repair and/or reinforcement of existing reinforced concrete structures. This work focuses on reinforcing the load-carrying capacity in shear of existing reinforced concrete beams, for which there currently exist various reinforcement technologies. The applicability of a particular type of reinforcement depends, among other factors, on the physical conditions and mechanical properties of the original element, physical space limitations, available technology at the construction site, and costs. Among the new advances in reinforcement methodologies is the use of steel fiber-reinforced concrete (SFRC) for jacketing or thickening, a material that due to its mechanical properties, durability and constructability is suitable for its use in shear reinforcement. However, its use is not widespread and information regarding its behavior as a reinforcement methodology is scarce. This work compares different shear reinforcement methodologies, in order to evaluate the suitability of SFRC as an alternative to existing methodologies and to identify the aspects in which it is necessary to deepen knowledge in order to ensure its applicability.